Pengaruh Pemberian Core Stability Exercise UntukPeningkatan Keseimbangan Dinamik Pada Pemain SepakBola Putra Maospati Di Kabupaten Magetan - Rini, Galuh Lubrika Chandra; , Dwi Rosella Komalasari S.Fis., M.Fis (2016)
Background: football is one of the most popular sports in Indonesia all walks of life, from children to adults especially men. Football players need physical ability elements that can give impact on the skills of football players. The quality of the basic engineering skills to play any game of physical condition factors, namely the speed, accuracy, strength, flexibility, agility, balance, endurance, coordination, and reaction. balance is the ability in maintaining posture and position the body properly at the time of standing (static balance) or when performing the movement (dynamic balance). Balance serves to reduce the risk of injury, improve the work of the muscles. There are many methods of exercise to improve balance, including the core stability exercise. Core stability Exercise illustrates the ability to control the position and movement of the middle part of the body. Objective: this research aims to know the influence of core stability excercise to improve dynamic balance on the football player's son maospati in magetan. Results: core stability exercise after exercise 2 times for 4 weeks, obtained as a result of the treatment with the highest significance of the anterior right (p) = 0.005, anterior to the left (p) = 0.003, posteromedial right (p) = 0.007, posteromedial left (p) = 0.005, medial right of 0,018 = (p), medial to the left (p) = 0,009 or p 0.05 then can be withdrawn < conclusions the existence of core stability exercises influence the awarding of the exercise. Whereas in the control group obtained the result value of the significance of the anterior right (p) = 0,317, anterior to the left (p) = 1,000, posteromedial right (p) = 1,000, posteromedial left (p) = 0,317, medial right (p) = 0,317, medial to the left (p) = 0.180 a conclusion can be drawn then the lack of influence on the control group. Conclusion: the granting practice Core stability exercise in group treatment can increase the dynamic balance on the football player's son at maospati, Magetan while the absence of influence of the dynamic balance of the improvement in the control group not given core stability exercise.